Impact of Drain Placement on Postoperative Complications after Thyroidectomy for Substernal Goiter - Waqar, Usama; Hameed, Ayesha Nasir; Angez, Meher; Kumar, Sudhesh; Arshad, Hajra; Siddiqui, Marium Tariq; Khan, Hira; Viquar, Werdah; Abbas, Aiza; Javid, Arsalan; Iftikhar, Haissan; Abbas, Syed Akbar; Naz, Huma; Saleem, Sarah (International Archives of Otorhinolaryngology, 2024)
Introduction Despite the evidence against drain placement after thyroidectomy, there is a lack of consensus on drain use in patients with substernal goiter.Objective To assess the factors that increase the likelihood of drain placement and its impact on postoperative hematoma and other 30-day complications among adult patients undergoing thyroidectomy for substernal goiter.Methods A retrospective cohort study that used data from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP). Adult patients (aged ≥ 18 years) who underwent elective thyroidectomy for substernal goiter from 2016 to 2020 were included. Cases with closed suction neck drains placed upon completion of surgery were included in the drain group, and the remaining cases formed the nondrain group.Results A total of 1,229 patients were included (46.5% with drain placement). The factors that increased the likelihood of drain placement included body mass index (BMI) ≥ 30 kg/m2, score between 3 and 5 on the American Society of Anesthesiologists (ASA) physical status classification, sternal split/transthoracic surgical approach, operative time ≥ 90 minutes, and surgery conducted by otolaryngologists. Patients with clean-contaminated or contaminated wound classifications were less likely to be submitted to drain placement. In addition, drain use had no impact on postoperative hematoma formation but was found to independently increase the risk of prolonged length of hospital stay.Conclusion Thyroidectomy without drain placement might be safe for substernal goiter. However, this decision should be individualized for each patient.Level Of Evidence: 3
Keywords: drainage; hematoma; substernal goiter; thyroid; thyroid surgery